Teaching Immigration Issues in Elementary School Classrooms on the US/Mexico Border: Transborder Pedagogy and Its Significance - Cashman, Timothy G (Journal of Interdisciplinary Studies in Education, 2022)
This case study uncovers how controversial issues such as the recent influx of refugees and immigrants were being addressed in upper elementary classrooms on the United States (US) side of the US/Mexico border. Public school administrators and sixth-grade teachers from two school sites participated. Transborder pedagogy contextualized the findings of the research. With the COVID-19 pandemic, classroom discussions of border issues have been superseded with other concerns. This research underscores the immediacy of transborder pedagogy during times of uncertainty.